2018
DOI: 10.1063/1.5010246
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of choline:urea and choline:oxalic acid deep eutectic solvents at 338 K

Abstract: 1:2 Choline chloride:urea and 1:1 choline chloride:oxalic acid deep eutectic solvents (DES) are compared at 338 K using liquid-phase neutron diffraction with H/D isotopic substitution to obtain differential neutron scattering cross sections and fitting of models to the experimental data using Empirical Potential Structure Refinement (EPSR). In comparison to the previously reported study of choline chloride:urea at 303 K, we observed significant weakening and lengthening of choline-OH•••Cland choline-OH•••hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 38 publications
7
39
0
1
Order By: Relevance
“…2b, or a near-ideal behaviour. This suggests that the hydroxyethyl group present in cholinium chloride allows for stronger interactions in the pure substance, either in the form of OH-Cl interactions between cation and anion, as suggested by Hammond et al [29] et al, or in the form of hydrogen bonding between cations (OH-OH), as recently proposed by Knorr et al [30] et al and Gilmore et al [31] et al This explains cholinium chloride positive deviations from ideality, while the cations in the alkylammoniumbased ionic solids cannot participate in hydrogen bonding nor offer any other type of specific interactions. Particularly, the [N 1,1,1,1 ]Cl salt used in the four systems above has no centres capable of specific interactions other than coulombic.…”
Section: Resultsmentioning
confidence: 74%
“…2b, or a near-ideal behaviour. This suggests that the hydroxyethyl group present in cholinium chloride allows for stronger interactions in the pure substance, either in the form of OH-Cl interactions between cation and anion, as suggested by Hammond et al [29] et al, or in the form of hydrogen bonding between cations (OH-OH), as recently proposed by Knorr et al [30] et al and Gilmore et al [31] et al This explains cholinium chloride positive deviations from ideality, while the cations in the alkylammoniumbased ionic solids cannot participate in hydrogen bonding nor offer any other type of specific interactions. Particularly, the [N 1,1,1,1 ]Cl salt used in the four systems above has no centres capable of specific interactions other than coulombic.…”
Section: Resultsmentioning
confidence: 74%
“…This view is only partially supported by the neutron diffraction study of Hammond and colleagues, 31 performed at 303 K, describing a ''radially layered sandwich structure'' where the cholinium cation's -OH and urea's -NH moieties strongly interact with the chloride anion while maintaining softer choliniumÁ Á Áurea and ureaÁ Á Áurea contacts. Using the same technique, Gilmore and co-workers 32 showed that at 338 K the OHÁ Á ÁCl correlation is weakened in favour of forming OHÁ Á ÁOH contacts, while the ureaÁ Á ÁCl interaction remains dominant. Charge transfer between the chloride anion and the hydrogen bond donor was initially proposed by Carriazo et al 39 as constituting the main driver for the melting point depression, yet his view has since been disputed by Zahn and co-workers' ab initio molecular dynamics simulation, 20 suggesting that charge transfer occurs mainly between the cation and the anion.…”
Section: Introductionmentioning
confidence: 98%
“…[2,3,[18][19][20] Calculations on DESs are rather sparse compared to experiments and often concentrate on the understanding of the hydrogen bonding behavior since a plethora of hydrogen bonds are available, examples are Refs. [5,18,[21][22][23][24].A very important kind of nanostructuring, namely, molecular ionic clusters within a complex and disordered hydrogen bonding network was observed by Edler and coworkers. [25][26][27] Biswas and coworkers found various type of aggregats depending on the anion and temperature.…”
mentioning
confidence: 97%
“…[2,3,[18][19][20] Calculations on DESs are rather sparse compared to experiments and often concentrate on the understanding of the hydrogen bonding behavior since a plethora of hydrogen bonds are available, examples are Refs. [5,18,[21][22][23][24].…”
mentioning
confidence: 99%